The important values of architectural Baghdadi heritage - Ismail, Sumarni; Akram, Omar Khasro; Utaberta, Nangkula; Mohd Yunos, Mohd Yazid; Ismail, Nor Atiah; Mohd Ariffin, Noor Fazamimah (American-Eurasian Network for Scientific Information, 2015)
This research addresses the importance values of the architectural heritage, existing in the Al-Baghdadi, where are highlighted the houses design, distinguished in two main types (traditional houses and the use of Mashrabiya in Baghdadi architectural heritage). It is essential to understand their general characteristics and also their cultural proprieties, studying not just their architecture and construction, but also their environmental properties, where is possible to understand the different purposes of the Mashrabiya such as protection fromthe summer hot sun. This papers aims also to identify the factors that led to occurrence of vandalism in architectural heritage of Baghdadi as well as enumerate some actions in a way to maintain and rehabilitate such heritage, preventing their degradation.